Subculture of alcohol and drug dependence - Köknel, Özcan (Journal of Dependence, 2001)
Subculture is the different and separated culture in the common cultural structure. Subculture of alcohol and drug dependence is a marked difference from co-mon cultural structure, such as: the aims, the expectations, the behaviours, the attitudes, the actions, the norms, the values, the dress, the arts the musics and particularly thel life styles and language. The primary factors of alcohol and drug depencese is psycho-social characteristics of young peoples. Alcohol and drug depencese, is an accepted and expected mode of problem-solving in these young peoples and often a feature of group dynamics. It should be noted that, Jargon the vocabulary of a specialized language is important manifestation of the subculture of alcohol and drug dependence.
Keywords: Subculture; dependence; young peoples; group dynamics; jargon